Penggunaan Model Pembelajaran Outdoor Learning terhadap Kemampuan Menulis Karangan Sederhana Bahasa Jerman Siswa - Aghe, Karolina A.E; Saleh, Nurming (Universitas Negeri Makassar, 2018)
This study aims to obtain data on the effectiveness of the use of Outdoor Learning learning models on the ability to write simple essays of Class XII Students of SMAK St. Fransiskus Saverius Ruteng, Manggarai Regency, East Nusa Tenggara, The method of this research is the experimental method with One Group Pretest Posttest design. The data collection technique used is the test The ability to write simple essays. Data were analyzed using t test. The population in this study were students of class XII of SMAK St. Fransiskus Saverius Ruteng which consists of one class of 28 people. The sample of this study is a total sample. The results of the data analysis showed th (6,21)> tt (2,052) at a significant level of 0.05. The results showed that the use of Outdoor Learning learning models was effective against Simple Writings Writing Ability of German students.